Comparative study of stability of soluble and cell wall invertase from Saccharomyces cerevisiae. Issue 3 (16th March 2017) - Margetić, Aleksandra; Vujčić, Zoran
ABSTRACT: Yeast Saccharomyces cerevisiae is the most significant source of enzyme invertase. It is mainly used in the food industry as a soluble or immobilized enzyme. The greatest amount of invertase is located in the periplasmic space in yeast. In this work, it was isolated into two forms of enzyme from yeast S. cerevisiae cell, soluble and cell wall invertase (CWI). Both forms of enzyme showed same temperature optimum (60°C), similar pH optimum, and kinetic parameters. The significant difference between these biocatalysts was observed in their thermal stability, stability in urea and methanol solution. At 60°C, CWI had 1.7 times longer half-life than soluble enzyme, while at 70°C CWI showed 8.7 times longer half-life than soluble enzyme. After 2-hr of incubation in 8 M urea solution, soluble invertase and CWI retained 10 and 60% of its initial activity, respectively. During 22 hr of incubation of both enzymes in 30 and 40% methanol, soluble invertase was completely inactivated, while CWI changed its activity within the experimental error. Therefore, soluble invertase and CWI have not shown any substantial difference, but CWI showed better thermal stability and stability in some of the typical protein-denaturing agents.